Spatial and seasonal use of habitat by birds in northern Nigeria - Muhammad, Sulaiman I.; Then, Amy Yee Hui; Ramli, Rosli (Taylor & Francis, 2018)
Capsule: Although woodland habitat supports higher avian species diversity and abundance, shrubland may be more important for migratory species. Aims: To investigate the use of habitat, site and season by bird species according to feeding guild, residence status and population trend in Dutse, Northern Nigeria. Methods: A point transect was used to count and identify birds between 0630 and 1100 hours from August 2015 to February 2016 across habitats, sites and seasons in Dutse. Results: Frugivore abundance was significantly higher in woodland habitat. The woodland and shrubland habitats had a higher proportion of resident and migratory species, respectively. Birds with stable population trends were more abundant in woodland, whereas the abundance of birds with decreasing trends were generally similar across most sites. Most of the birds with decreasing trends were migratory species. The dry season had a higher abundance and diversity of birds across different feeding guilds, residence status and population trend status than the wet season. Conclusion: Both woodland and shrubland in Dutse were important bird habitats, but migrant species preferentially used shrubland. The shrubland habitat and the dry season should be prioritized for conservation consideration, especially for migrant birds in Dutse.